From Rhetoric to Reality: Tackling Poverty and Inequality Through a Just transition in Scotland (Concept: The Journal of Contemporary Community Education Practice Theory, 2025)
This article examines the intersection of poverty, inequality, and climate policy in Scotland. It argues that the shift to a low carbon economy offers a transformative opportunity to address structural social injustices that have persisted for decades. Drawing on government frameworks, civil society research, and comparative policy examples, the paper contends that Scotland’s just transition must embed social equity from the outset. It identifies income security, gender-responsive care infrastructure, participatory democracy, and fiscal justice as essential pillars of an inclusive transformation. The analysis demonstrates that poverty is a consequence of political design rather than individual failure, and that only a whole-economy approach can deliver both environmental and social sustainability.